2013
DOI: 10.1159/000352020
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation in Amyloid-β-Related Angiitis Correlates with Decreased Parenchymal Amyloid-β Plaque Load

Abstract: Background: Primary angiitis of the central nervous system (PACNS) is a rare but serious condition. A fraction of patients suffering from PACNS concurrently exhibit pronounced cerebral amyloid angiopathy (CAA) which is characterized by deposits of amyloid-β (Aβ) in and around the walls of small and medium-sized arteries of the brain. PACNS with CAA has been identified as a distinct disease entity, termed Aβ-related angiitis (ABRA). Evidence points to an immune reaction to vessel wall Aβ as the trigger of vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…This case therefore adds further support to a growing body of literature linking CAA-ri to radiological features described as ARIA [10]. Whilst the precise underlying pathogenetic mechanisms are not yet fully understood, previous observations of CD68 + macrophages and CD4 + Tcell recruitment at sites of Aβ-related angiitis [11,12] and CSF anti-Aβ autoantibodies in patients with spontaneous CAA-ri [6,13] support the notion of an autoimmune response against vascular Aβ [10].…”
Section: Discussionsupporting
confidence: 71%
“…This case therefore adds further support to a growing body of literature linking CAA-ri to radiological features described as ARIA [10]. Whilst the precise underlying pathogenetic mechanisms are not yet fully understood, previous observations of CD68 + macrophages and CD4 + Tcell recruitment at sites of Aβ-related angiitis [11,12] and CSF anti-Aβ autoantibodies in patients with spontaneous CAA-ri [6,13] support the notion of an autoimmune response against vascular Aβ [10].…”
Section: Discussionsupporting
confidence: 71%
“…First, like in immunotherapy, the acute phase of CAA-ri is characterized by a specific immune reaction mediated by an increased amount of autologous CSF antibodies against the perivascular deposited Aβ typical of CAA ( 13 , 16 , 21 , 44 46 ). Although observed in a single case study, autoantibodies have been found to be intrathecally produced and specifically increased only in CSF, while no changes has been found in the plasma, thus reflecting the immune/inflammatory mechanisms restricted to the brain ( 13 ).…”
Section: Anti-aβ Antibodies As Biomarker For Ariamentioning
confidence: 99%
“…Slides were pre‐screened by light microscopy and three representative regions of interest (ROI; 0.5 mm 2 ) were electronically scanned at high magnification (×400) as high‐resolution images (1900 × 1200 pixels), using NanoZoomer 2.0‐HT (Hamamatsu Ltd., Hamamatsu, Japan). Immunosignals were morphometrically assessed (using ImageJ image analysis software, Wayne Rasband, Version 1.51d, Bethesda, Maryland, USA), revealing the area fraction (the percentage of pixels that have been highlighted in red in thresholded images), according to established protocols …”
Section: Methodsmentioning
confidence: 99%
“…Immunosignals were morphometrically assessed (using ImageJ image analysis software, Wayne Rasband, Version 1.51d, Bethesda, Maryland, USA), revealing the area fraction (the percentage of pixels that have been highlighted in red in thresholded images), according to established protocols. 38…”
Section: Neuropathological Investigations and Immunohistochemistrymentioning
confidence: 99%